And Then There Was Intersubjectivity: Addressing Child Self and Mutual Dysregulation During Traumatic Play: In Memory of Louis Sander. Issue 1 (2nd January 2019) - Schechter, Daniel S.
ABSTRACT: This article asserts that a traumatized mother, to maintain her psychobiological homeostasis, must avoid intersubjective connection with a child who is seeking it to regulate his own distress. In this case, what Lou Sander described as a "moment of meeting" cannot take place (Sander, 1995, p. 590). Case examples are used to illustrate how, when all are together in the consulting room, the reflective, mutually regulating therapist can facilitate moments of meeting between therapist, a mother who has been subjected to interpersonal violence, and her child, who has similarly been traumatized. Furthermore, I show how the therapist, in the face of the child's traumatic reenactment in play that can further trigger and dysregulate the traumatized parent, can intervene to coconstruct meaning, for both the traumatized child and mother, obviating mother's need to avoid the child's distress and post-traumatic re-experiencing. This allows meeting to occur, reordering the implicit relational knowing of both mother and child.